Rapid response to treatment with thalidomide in an adolescent with generalized discoid lupus erythematosus. Issue 1 (2nd December 2019) - Tran, Benjamin; Yazdani Abyaneh, Mohammad‐Ali; Wu, Julia
Abstract: Discoid lupus erythematosus (DLE) is the most common variant of cutaneous chronic lupus erythematosus (CLE). Sun protection, topical corticosteroids, and antimalarials constitute the first‐line options for treatment. In refractory cases, alternative antimalarials, methotrexate, retinoids, and thalidomide have been utilized. We present a case of an adolescent patient with generalized DLE responding rapidly to thalidomide.